2019
DOI: 10.1016/j.coal.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Estimating permeability in shales and other heterogeneous porous media: Deterministic vs. stochastic investigations

Abstract: With increasing global energy demands, unconventional formations, such as shale rocks, are becoming an important source of natural gas. Extensive efforts focus on understanding the complex behavior of fluids (including their transport in the sub-surface) to maximize natural gas yields. Shale rocks are mudstones made up of organic and inorganic constituents of varying pore sizes (1-500nm). With cutting-edge imaging technologies, detailed structural and chemical description of shale rocks can be obtained at diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…29,30 Apostolopoulou et al recently implemented stochastic kinetic Monte Carlo (KMC) simulations to study fluid transport across pore networks. 31 KMC methods can access long time scales (up to ms and, in some cases, hours) and large spatial scales (nm to μm) at comparatively low computational expense. 32,33 For example, in a bottom-up 1D approach, Apostolopoulou et al 1) used previously reported MD data to inform the KMC model, 2) simplified a 3D, 2-phase system consisting of confined liquid water and methane into a 1D problem, and 3) obtained KMC transport data in quantitative agreement with atomistic MD simulations at a fraction of the computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Apostolopoulou et al recently implemented stochastic kinetic Monte Carlo (KMC) simulations to study fluid transport across pore networks. 31 KMC methods can access long time scales (up to ms and, in some cases, hours) and large spatial scales (nm to μm) at comparatively low computational expense. 32,33 For example, in a bottom-up 1D approach, Apostolopoulou et al 1) used previously reported MD data to inform the KMC model, 2) simplified a 3D, 2-phase system consisting of confined liquid water and methane into a 1D problem, and 3) obtained KMC transport data in quantitative agreement with atomistic MD simulations at a fraction of the computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive understanding of the fundamental mechanisms responsible for carbon bearing-fluid migration in the presence of CO 2 /H 2 S is crucial for risk assessment and site selection for geologic CCS, monitoring H 2 S emissions, and perhaps identifying innovative enhanced oil recovery (EOR) processes that use CO 2 and H 2 S. , Because a thorough quantification of the phenomena that govern fluid transport in the complex heterogeneous pore networks found in organic-rich shale caprocks, which consist of crowded nanopores that provide poor connections between dispersed pockets of organic matter, remains elusive, because of practical difficulties in observing fluid transport in such complicated systems, computational approaches could be helpful. …”
mentioning
confidence: 99%
“…Our KMC approach, applied to 1D, 2D and 3D pore networks, is described by Apostolopoulou et al (2017Apostolopoulou et al ( , 2019a. The underlying model of the KMC simulation is the Master equation (Eq.…”
Section: D Kmc Model For Fluid Diffusionmentioning
confidence: 99%